Pengembangan video pembelajaran animasi berbasis website s.id "KhalifaToon" tentang Khalifah pada pembelajaran PAI Kelas 5 SD - Hikmah, Dela Anita; Hayatun Khaira; Sarah Mulkiyati Dzikro; Ani Nur Aeni; Holil, M. (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2026)
In the digital era, the utilization of technology in learning is an essential need to improve the educational quality. This study aims to develop and evaluate the effectiveness of the s.id website-based animated learning video “KhalifaToon” in supporting students’ understanding of caliph material in learning Islamic Religious Education (PAI) grade V in elementary school. The research method used is ADDIE, contains Analysis, Design, Development, Implementation, and Evaluation. Data were collected through media and material expert validation tests, as well as trials to students as users. The results showed that the animation learning video developed met the quality standards of interactive learning media with a high level of validity based on expert assessments and positive responses from students. The implementation of this media is proven to increase student involvement in learning and help concept understanding more effectively than conventional methods. Thus, the use of website-based interactive animation-based media in PAI learning is recommended as an innovative strategy to improve learning effectiveness.